Morphology and reproduction of Porphyra pseudolanceolata Krishnamurthy (Bangiales, Rhodophyta) in the Peruvian coast - Távara, Caleen (1992)
This study on Porphyra pseudolanceolata Krish. has as its principal objective to determine if the reason, for an observed abundance of small individuals, growing on the same substratum is due to the presence of neutrospores and, thereby, to asexual reproduction. Other objectives were to study the difierentiation of reproductive structures on both monoecious and dioecious individuals, and to investigate the life cycle and ecology of this species which like Porphyra columbina Mont., is used for human consumption.